Wisdom's Wittgenstein - Milkov, Nikolay (Wittgenstein and Other Philosophers: His Influence on Historical and Contemporary Analytic Philosophers, 2 vol., Volume II)
In 1921, John Wisdom (1904–1993) became a member of Fitzwilliam House, Cambridge, where he read philosophy and attended lectures by G. E. Moore, C. D. Broad, and J. E. McTaggart. He received his BA in 1924, after which he worked for five years at the National Institute of Industrial Psychology. From 1929 to 1934, Wisdom was a Lecturer in the department of logic and metaphysics at the University of St Andrews and a colleague of G. F. Stout. After the publication of his book Interpretation and Analysis (1931) and five articles on “Logical Constructions” in Mind (1931–3), Wisdom became a Lecturer in Moral Sciences in Cambridge and a Fellow of Trinity College. This gave him the opportunity to gain first-hand knowledge of Wittgenstein’s philosophy. Since nothing by Wittgenstein but Tractatus appeared in print for decades, Wisdom’s publications of these years were—mistakenly—read as portents of the new ideas of Wittgenstein himself. The publication of Wittgenstein’s Philosophical Investigations in 1953 brought with it, among other things, the fall of Wisdom’s popularity.
Keywords: elucidation; facts; Frege; language; metaphysics; G. E. Moore; Russell; Stebbing; John Wisdom; Wittgenstein

Stebbing's Wittgenstein - Milkov, Nikolay (Wittgenstein and Other Philosophers: His Influence on Historical and Contemporary Analytic Philosophers, vol. II)
Susan Stebbing wrote only once on Wittgenstein, in her paper ‘Logical Positivism and Analysis’ (1933). The paper was unusually critical of Wittgenstein. It put the Cambridge analytic philosophy of Moore and Russell in a sharp opposition to the positivist philosophy of the Vienna Circle, in which Stebbing included Wittgenstein. Whereas the positivists were interested in analysing language, the Cambridge realists were analysing facts. To be more explicit, the analytic philosophers were engaged in directional analysis, which seeks to illuminate (to elucidate) the multiplicity of the analysed facts. In contrast, positivists aimed at a final analysis that proves that there are simples. Stebbing’s sympathies were clearly on the side of the Cambridge realists. The important implication of Stebbing’s paper was that it urged Wittgenstein to change the style of his philosophy, abandoning those points which allegedly connected him with the Vienna Circle.
Keywords: directional analysis; elucidation; facts; metaphysics; G. E. Moore; Russell; Stebbing; John Wisdom; Wittgenstein

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

A configuration-based recommender system for supporting e-commerce decisions - Scholz, Michael; Dorner, Verena; Schryen, Guido; Benlian, Alexander (European Journal of Operational Research)
Multi-attribute value theory (MAVT)-based recommender systems have been proposed for dealing with issues of existing recommender systems, such as the cold-start problem and changing preferences. However, as we argue in this paper, existing MAVT-based methods for measuring attribute importance weights do not fit the shopping tasks for which recommender systems are typically used. These methods assume well-trained decision makers who are willing to invest time and cognitive effort, and who are familiar with the attributes describing the available alternatives and the ranges of these attribute levels. Yet, recommender systems are most often used by consumers who are usually not familiar with the available attributes and ranges and who wish to save time and effort. Against this background, we develop a new method, based on a product configuration process, which is tailored to the characteristics of these particular decision makers. We empirically compare our method to SWING, ranking-based conjoint analysis and TRADEOFF in a between-subjects laboratory experiment with 153 participants. Results indicate that our proposed method performs better than TRADEOFF and CONJOINT and at least as well as SWING in terms of recommendation accuracy, better than SWING and TRADEOFF and at least as well as CONJOINT in terms of cognitive load, and that participants were faster with our method than with any other method. We conclude that our method is a promising option to help support consumers' decision processes in e-commerce shopping tasks.
Keywords: E-Commerce; Recommender System; Attribute Weights; Configuration System; Decision Support

Spielend Lehrer/in werden: problembasiertes Lernen mit virtuellen Schülerinnen/Schülern. - Praetorius, Saskia; Al-Kabbani, Daniel; Bohndick, Carla; Hilkenmeier, Johanna; König, Sebastian T.; Müsche, Hannah S.; Sommer, Sabrina; Klingsieck, Katrin B. (Zeitschrift für Hochschulentwicklung)
Über das Lehramtsstudium sollen Studierende unter anderem dazu befähigt werden, die Leistung ihrer Schüler/innenzu bewerten. Dazu müssen sie Einflussfaktoren auf Schulleistung kennen und diese richtig diagnostizieren und fördern können. Mit diesem Beitrag wird eine game-und E-Learning-gestützte Lernumgebung vorgestellt, in der Studierende –anders als in vielen inputorientierten Seminarkonzepten –in einem virtuellen Klassenzimmer an realitätsnahen Fällen lernen,problembasiert zu diagnostizieren und zu fördern. Über denEinsatz der Lernumgebung in der Lehre wird berichtet, erste Rückmeldungen von Lehrenden und Studierenden werden erläutert und weitere Planungsschritte dargestellt.
Keywords: E-Learning; digitale Medien; problembasiertes Lernen; Lehrerbildung; Diagnostik

The Value of Self-Service: Long-Term Effects of Technology-Based Self-Service Usage on Customer Retention. - Scherer, Anne; Wünderlich, Nancy; Von Wangenheim, Florian (MIS Quarterly)
Advancements in information technology have changed the way customers experience a service encounter and their relationship with service providers. Especially technology-based self-service channels have found their way into the 21st century service economy. While research embraces these channels for their cost-efficiency, it has not examined whether a shift from personal to self-service affects customer–firm relationships. Drawing from the service-dominant logic and its central concept of value-in-context, we discuss customers’ value creation in self-service and personal service channels and examine the long-term impact of these channels on customer retention. Using longitudinal customer data, we investigate how the ratio of self-service versus personal service use influences customer defection over time. Our findings suggest that the ratio of self-service to personal service used affects customer defection in a U-shaped manner, with intermediate levels of both self-service and personal service use being associated with the lowest likelihood of defection. We also find that this effect mitigates over time. We conclude that firms should not shift customers toward self-service channels completely, especially not at the beginning of a relationship. Our study underlines the importance of understanding when and how self-service technologies create valuable customer experiences and stresses the notion of actively managing customers’ cocreation of value.
Keywords: customer defection; customer retention; e-service; longitudinal; Self-service; value-in-context

Optimierung des einsatzbezogenen Lernens durch Wissensidentifikation - Pottebaum, Jens
Keywords: Arbeitsorganisation; E-Learning; Lernorganisation; Lerntechnik; Wissensmanagement

Weblogs zur Unterstützung der Theorie-Praxis-Integration in der Wirtschaftslehrenden-Ausbildung - Jenert, Tobias; Gebhardt, Anja; Käser, Reto (Zeitschrift für E-Learning)
Eine zentrale Herausforderung in der Ausbildung angehender Wirtschaftslehrpersonen stellt die sinnvolle Verknüpfung von Theorie- und Praxiserfahrungen dar. Im Rahmen der Ausbildung angehender Wirtschaftslehrpersonen an der Universität St. Gallen wird eine Lernumgebung gestaltet, die eine Verschränkung von Theorie- und Praxiserfahrungen ermöglichen soll. Die Lernprozesse der Studierenden werden dabei durch didaktisch angeleitete Weblogarbeit unterstützt. Trotz der Lernchancen, die sich aus einer Verknüpfung von theoretischen und praktischen Lernphasen ergeben, schätzen die Studierenden den Nutzen der Weblogarbeit als äusserst gering ein. Die Studierenden bei der reflexiven Integration praxisnaher und theoretischer Lernerfahrungen zu unterstützen, ist eine Herausforderung, die dezidierter Anleitung und Förderung durch die Lehrpersonen bedarf
Keywords: Weblog; Blog; e-learning; TEL; higher education; business education

Measuring eTrust in distributed systems - General Concept and Application to Internet Voting - Volkamer, Melanie; Schryen, Guido (Proceedings of the 23rd Bled eConference)
Emerging digital environments and infrastructures, such as distributed services and computing services, have generated new options of communication, information sharing, and resource utilization in past years. Different distributed trust concepts are applied to increase trust in such systems. However, these concepts yield to rather complex architectures which make it difficult to determine which component or system needs to be trusted. This paper presents a novel trust measurement method for distributed systems which enables the t identification of weak points in the overall system architecture. The measurement method includes the specification of a formal trust language and its representation by means of propositional logic formulas. The applicability of the proposed concepts is demonstrated by conducting a case study on the Internet voting system that was used in the 2007 parliamentary elections in Estonia.
Keywords: distributed trust concepts; measuring etrust; Internet voting

Security in Large-Scale Internet Elections: A Retrospective Analysis of Elections in Estonia, The Netherlands, and Switzerland - Schryen, Guido; Rich, Eliot (IEEE Transactions on Information Forensics & Security)
Remote voting through the Internet provides convenience and access to the electorate. At the same time, the security concerns facing any distributed application are magnified when the task is so crucial to democratic society. In addition, some of the electoral process loses transparency when it is encapsulated in information technology. In this paper, we examine the public record of three recent elections that used Internet voting. Our specific goal is to identify any potential flaws that security experts would recognize, but may have not been identified in the rush to implement technology. To do this, we present a multiple exploratory case study, looking at elections conducted between 2006 and 2007 in Estonia, Netherlands, and Switzerland. These elections were selected as particularly interesting and accessible, and each presents its own technical and security challenges. The electoral environment, technical design and process for each election are described, including reconstruction of details which are implied but not specified within the source material. We found that all three elections warrant significant concern about voter security, verifiability, and transparency. Usability, our fourth area of focus, seems to have been well-addressed in these elections. While our analysis is based on public documents and previously published reports, and therefore lacking access to any confidential materials held by electoral officials, this comparative analysis provides interesting insight and consistent questions across all these cases. Effective review of Internet voting requires an aggressive stance towards identifying potential security and operational flaws, and we encourage the use of third party reviews with critical technology skills during design, programming, and voting to reduce the changes of failure or fraud that would undermine public confidence.
Keywords: e-voting; Internet voting; Internet election; security; verifiability; RIES; Estonia; Neuchâtel

Practical Security of Large-scale Elections: An Exploratory Case Study of Internet Voting in Estonia - Schryen, Guido (7th Workshop on e-Business (WEB 2008, AIS Special Interest Group on E-Business))
The Estonian parliamentary election in 2007 is regarded as a success story of large-scale Internet elections. I use this election in a single case study on practical security to show that low quality of security and its management does not necessarily prevent large-scale Internet elections from being conducted. I also provide research propositions with regard to future challenges for large-scale Internet elections.
Keywords: Internet voting; large-scale election; Estonian parliamen- tary election; security; security management

Einsatz von E-Portfolios zur Förderung von studentischen Lerngemeinschaften im Hochschulstudium. - Sporer, Thomas; Jenert, Tobias; Strehl, Bernhard; Noack, Patrick Ole (DeLFI Workshops)
Keywords: E-Portfolios; Lerngemeinschaften; Praxisgemeinschaften; Projektgruppen; Hochschulstudium; informelles Lernen

Student Learning Communities in the Project-Centered Study Program" Problem-Solving Competencies" - Sporer, Thomas; Heinze, Nina; Jenert, Tobias; Reinmann, Gabi
Keywords: Problem Solving Competencies; E-Portfolio

Do anti-spam measures effectively cover the e-mail communication network? A formal approach - Schryen, Guido (The Journal of Information Systems Security (AIS Special Interest Group in Security))
Spam e-mails have become a serious technological and economic problem. Up to now, by deploying complementary anti-spam measures, we have been reasonably able to withstand spam e-mails and use the Internet for regular communication. However, if we are to avert the danger of losing the Internet e-mail service in its capacity as a valuable, free and worldwide medium of open communication, anti-spam activities should be performed more systematically than is currently the case regarding the mainly heuristic, anti-spam measures in place. A formal framework, within which the existing delivery routes that a spam e-mail may take, and anti-spam measures and their effectiveness can be investigated, will perhaps encourage a shift in methodology and pave the way for new, holistic anti-spam measures. This paper presents a model of the Internet e-mail infrastructure as a directed graph and a deterministic finite automaton and draws on automata theory to formally derive the spam delivery routes. The most important anti-spam measures are then described. Methods controlling only specific delivery routes are evaluated in terms of how effectively they cover the modeled e-mail infrastructure; methods operating independently of any particular routes receive a more general assessment.
Keywords: e-mail; spam; e-mail infrastructure; anti-spam measures; spamming options

An e-mail honeypot addressing spammers' behavior in collecting and applying addresses - Schryen, Guido (Proceedings of the 6th IEEE Information Assurance Workshop)
Spam has become one of the most annoying and costly phenomenon in the Internet. Valid e-mail addresses belong to the most valuable resources of spammers, but little is known about spammers? behavior when collecting and harvesting addresses and spammers? capabilities and interest in carefully directed, consumer-oriented marketing have not been explored yet. Gaining insight into spammers? ways to obtain and (mis)use e-mail addresses is useful in many ways, e.g. for the assessment of the effectiveness of address obscuring techniques and the usability and necessity of hiding e-mail addresses on the Internet. This paper presents a spam honeypot project in progress addressing these issues by systematically placing e-mail addresses in the Internet and analyzing received e-mails. The honeypot?s conceptual framework, its implementation, and first empirical results are presented. Finally, an outlook on further work and activities is provided.
Keywords: Spam; ham; e-mail; honeypot; address obscuring technique; address taxonomy

Effektivität von Lösungsansätzen zur Bekämpfung von Spam - Schryen, Guido (Wirtschaftsinformatik)
Spam als unerwünschte Massen-E-Mail hat die Grenze von der Belästigung zur ökonomischen Relevanz längst überschritten. Ihr relativer Anteil am gesamten, weltweiten E-Mail-Aufkommen stieg in den vergangenen Jahren auf mehr als 50% im Jahr 2003. Es entstehen jährlich volkswirtschaftliche Schäden in Milliardenhöhe. Zur Bekämpfung des Spam-Problems werden neben gesetzlichen Regelungen vor allem technische Lösungen eingesetzt, bei denen das Blockieren und Filtern von E-Mails in praktisch eingesetzten Anti-Spam-Systemen dominieren. Dieser Artikel führt in die Spam-Problematik ein und beschreibt, bewertet und klassifiziert die derzeit bedeutendsten Verfahren zur Bekämpfung von Spam.
Keywords: Spam; E-Mail; Spoofing; Blockieren; Filtern; Lightweight Mail Transfer Agent Authentication Protocol (LMAP)

Fighting Spam: Motivating an Account-based Approach - Schryen, Guido (Proceedings of the IADIS International Conference WWW/Internet 2004. vol. 2)
Spam as unsolicited e-mail to a large number of recipients is known to ecome an increasingly disturbing and costly issue of electronic business and internet traffic. Mainly technical-oriented approaches are applied with a focus on blocking, filtering, and authentication mechanisms based on the domain name system. They come along with different drawbacks and have all low effectiveness in common. The article sketches these approaches, shows its limitations, and proposes an account-based approach where the number of e-mails per day and account is restricted.
Keywords: e-mail; spam; filtering; blocking; LMAP; SMTP account

E-Democracy: Internet Voting - Schryen, Guido (Proceedings of the IADIS International Conference WWW Internet 2003. vol. 2)
Voting via the Internet is part of electronic government and electronic democracy. However, there are many obstacles which have to be overcome, especially legal restrictions have to be transformed into technical and security solutions. In the first part the article discusses advantages and disadvantages of Internet elections, shows different application fields, and presents important international pilot schemes (political and business ones). in the second part, due to democratic basic principles, technological security aspects are worked out.
Keywords: Internet Voting; Online polls; E-Democracy; Security

Internet-Wahlen - Schryen, Guido (6. Internationale Tagung Wirtschaftsinformatik)
Zusammenfassung: Im Rahmen des E-Governments werden zunehmend Internetwahlen diskutiert. Der Beitrag diskutiert zunächst die Vor- und Nachteile derartiger Wahlen und zeigt Anwendungsgebiete sowie durchgeführte Pilotprojekte im politischen wie auch wirtschaftlichen Bereich auf. Im Rahmen eines Anforderungssystems werden anschließend aus demokratischen Wahlgrundsätzen sicherheitstechnologische Anforderungen herausgearbeitet. Zu deren Adressierung werden kryptographischen Wahlkonzepte herangezogen, von denen die wichtigsten vorgestellt werden. Aufgrund der Komplexität der Anforderungslandschaft wird ein sicherheitstechnologisches Strukturmodell vorgestellt, das insbesondere dazu dient, die Sicherheit(skomponenten) eines Wahlsystems systematisch mit den Anforderungen abzugleichen. Der Artikel schließt mit einem Ausblick auf notwendige Untersuchungen.
Keywords: Internet-Wahlen; E-Democracy; Sicherheit; Kryptographie

Elektronisches Papier - Display-Technologie mit weitem Anwendungsspektrum - Schryen, Guido; Karla, Jürgen (Wirtschaftsinformatik)
Mit dem elektronischen Papier wird in der Displayforschung ein neuer materialtechnologischer Ansatz verfolgt: Elektronisches Papier besteht aus einer dünnen, flexiblen Folie, in der farbige Pigmente mittels elektrischer Felder ausgerichtet werden. Die Vorteile gegenüber traditionellen Technologien wie beispielsweise LCD-Displays bestehen zum einen in niedrigeren Herstellungskosten (niedrigere Produktionskosten und geringere Materialkosten) und einem geringeren Gewicht. Zum anderen entsteht eine bessere Lesbarkeit, da sich Reflexion, Kontrast und mögliche Betrachtungswinkel verbessern bzw. vergrößern. Diese Potenziale können bei Anzeigetafeln, Computerdisplays und mobilen Endgeräten ausgeschöpft werden. Mit der Eigenschaft, fast beliebige Materialien als Trägermedium zu verwenden, öffnet sich auch die Anwendungsmöglichkeit des biegsamen, elektronischen Mediums für Zeitungen und Zeitschriften. Die US-Unternehmen E Ink und Gyricon Media bieten eine zunehmend größere Produktpalette mit elektronischem Papier an.
Keywords: Elektronisches Papier; Elektronische Tinte; E Ink; Gyricon Media; Displays; Mobile Endger{\